2000
DOI: 10.1111/j.1651-2227.2000.tb00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in 11‐13‐year‐olds' physical activity

Abstract: Few children experience extended bouts of PA, and from 11-13 y, PA decreases, with more girls than boys becoming inactive. The data emphasize the importance of promoting active lifestyles during youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 17 publications
1
23
0
5
Order By: Relevance
“…A diminuição da AF com o aumento da idade, apesar de não ter acontecido no nosso estudo, tem sido descrita com frequência (Armstrong & Welsman, 2006;Armstrong, Welsman, & Kirby, 2000;Boreham & Riddoch, 2001;Yli-Piipari et al, 2012). Paralelamente a prevalência da adesão à prática desportiva também é menor à medida que a idade avança.…”
Section: Prática Desportivaunclassified
See 1 more Smart Citation
“…A diminuição da AF com o aumento da idade, apesar de não ter acontecido no nosso estudo, tem sido descrita com frequência (Armstrong & Welsman, 2006;Armstrong, Welsman, & Kirby, 2000;Boreham & Riddoch, 2001;Yli-Piipari et al, 2012). Paralelamente a prevalência da adesão à prática desportiva também é menor à medida que a idade avança.…”
Section: Prática Desportivaunclassified
“…Entre adolescentes com idades compreendidas entre 15 e 18 anos os padrões de AF vão decaindo, sobretudo nas meninas (Boreham & Riddoch, 2001) e a AF vigorosa regular apresenta um declínio constante entre os 12 até aos 21 anos, estabilizando entre os 30 e 64 anos (Caspersen, Pereira, & Curran, 2000). Num estudo longitudinal, no sentido de avaliar as alterações aos níveis de AF em crianças com idades dos 11 aos 13 anos, Armstrong et al (2000) descobriram as seguintes diminuições com a idade de 76.2 para 44.4% nos meninos e 73.5 para 31.6% nas meninas. Ainda constataram que com a idade de 11 anos 22.1% dos meninos e 29.6% das meninas não realizavam sequer 10 minutos de AF moderada por semana e com a idade de 13 anos os valores foram de 28.4 e 51.9% para meninos e meninas respetivamente.…”
Section: Prática Desportivaunclassified
“…13 Some authors found differences between the fitness of obese and nonobese children, others not. [14][15][16] The most popular direct instruments for assessing physical activity are questionnaires, observation and monitors like heart rate monitoring. In addition, the results of motor ability tests could be used as an indirect marker of activity or inactivity.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that information that is needed to inform health policies should come from longitudinal analysis (Armstrong, Welsman, & Kirby, 2000). Therefore, stronger evidence for any patterns of change in sedentary behaviour during adolescence may come from a review of longitudinal studies.…”
Section: Summary Of Sedentarism and Sedentary Behavioursmentioning
confidence: 99%